2011
DOI: 10.14712/18059694.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Duplex Ultrasonography and Magnetic Resonance Imaging in the Detection of Significant Renal Artery Stenosis

Abstract: IntroductionRenovascular hypertension (RVH) is one of the most common causes of secondary arterial hypertension. Renal artery stenosis (RAS) is caused by atherosclerosis in 90 % of the RVH patients and fibromuscular dysplasia is found in the great majority of the remaining cases (10). As the renal revascularization might improve renal function and blood pressure control, the screening for the presence of significant renal artery stenosis (RAS) is recommended in selected patients with arterial hypertension. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
(9 reference statements)
2
15
0
1
Order By: Relevance
“…This is comparable to success in other studies of renal Doppler ranging from 86% to 94% [5,7,15]. Of all RHDUS studies analyzed, 7% showed evidence of RAS.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is comparable to success in other studies of renal Doppler ranging from 86% to 94% [5,7,15]. Of all RHDUS studies analyzed, 7% showed evidence of RAS.…”
Section: Discussionsupporting
confidence: 82%
“…Univariate analysis in this study showed a significant association between previously documented hypertension and positive RDHUS for RAS (p=.018) and even stronger significance between hypertensive urgency or flash pulmonary edema on admission and positive RHDUS for RAS (p=.002). Examination for renal artery stenosis is indicated by resistant or poorly controlled blood pressure, coexisting atherosclerosis, kidney injury of unknown etiology, and atrophic or asymmetric kidneys [1,7]. This study confirms that poorly controlled hypertension or hypertensive urgency and/or flash pulmonary edema is a good indicator for a Doppler evaluation for RAS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Studies conducted using CCDS (mostly after 1993) generally set the cut-off at 180–200 cm/s [ 8 , 19 , 24 , 27 , 40 , 42 ]. As peak velocities are determined using receiver operating characteristics (ROC) curves, they also always represent an evaluation performed by the author to assess sensitivity or specificity, positive predictive value (PPV) or negative predictive value (NPV).…”
Section: Significance Of Color-coded Duplex Sonography In the Detectimentioning
confidence: 99%
“…As shown by other reports, 5,6,[12][13][14][21][22][23][24][25][26][27] this current study demonstrates the feasibility and reliability of RDU imaging in diagnosing RAS. There is no ideal screening test for RAS; whereas some reports advocate MRA, 28,29 others recommend CTA. 28,30 At the current time, however, when cost-effectiveness is crucial, the most important characteristic of any screening test for RAS is to provide enough sensitivity and to guide the need for additional diagnostic and therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%